Management of Bhagandara Fistula In Ano Under the Influence of Karanjadi Ghrita - Hemant Kumar Seetha, Dr (International Journal of Pharmaceutical & Biological Archive, 2013)
Management of Bhagandara Fistula In Ano Under the Influence of Karanjadi Ghrita